Penggunaan Container Pad pada Container Yard Ex. Semen Tonasa di Wilayah Pelabuhan Trisakti untuk Tipe Kontainer 20 feet dan 40 feet - Wahyu Arry Prabowo (Jurnal Teknologi Berkelanjutan, 2021)
Minimizing damage to the container yard area (container stacking), where the most extreme conditions occur when there are 4 containers placed close to one foot supporting at one point, and taking into account that each container is stacked 5 tiers with a weight of 30.48 tonf for the type of container is 40 feet and the weight is 24.0 tonf for the type of container 20 feet. So that in a set of container feet, the load can be accumulated 4 x [5 x (30,48)] / 4 = 152.4 tonf (40 feet) and 120.0 tonf (20 feet). This paper discusses the need for the use of container pads in the Modified Chicken Claw pavement system which is applied to the container yard ex area. Semen Tonasa Trisakti Harbor, where the determination of the pad points made 3 simulations, each simulation accommodated 24 points of Modified Chicken Claw Pipe (CAM). From the simulation is to determine the magnitude of the displacement and differential settlement that occurs due to the load of the container.